Electrode for all-solid-state battery, all-solid-state battery and method for producing same
Patent Information
- Application Number
- JP2022038266
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-11
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2042-03-11
AI Technical Summary
【0014】 本開示によれば、電池抵抗を低減することができる。
Smart Images

Figure 0007632354000005 
Figure 0007632354000001 
Figure 0007632354000002
Abstract
Description
[Technical field]
[0001] The present application relates to an electrode for an all-solid-state battery, an all-solid-state battery, and a method for producing the same. [Background technology]
[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. In the automobile industry, development of high-output, high-capacity batteries for electric vehicles and hybrid vehicles is also underway. Among various types of batteries, lithium-ion batteries are currently attracting attention because of their high energy density.
[0003] Currently commercially available lithium-ion batteries use electrolytes that contain flammable organic solvents, so they require improvements in structure and materials to prevent short circuits and the installation of safety devices to suppress temperature rises during short circuits. In contrast, all-solid-state batteries, which use a solid electrolyte layer to turn the electrolyte into a solid-state battery, do not use flammable organic solvents in the battery, so safety devices can be simplified and they are thought to be superior in terms of manufacturing costs and productivity.
[0004] In recent years, various techniques have been developed to improve the performance of all-solid-state batteries. Among them, there is a technique to reduce the battery resistance in order to improve the output. For example, Patent Document 1 discloses an all-solid-state battery having a solid electrolyte layer containing two types of solid electrolytes having different average particle sizes. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-157084 A Summary of the Invention [Problem to be solved by the invention]
[0006] In order to further reduce the battery resistance, the inventors applied the technology described in Patent Document 1 to the electrodes. As a result, it was confirmed that the battery resistance did not decrease. The inventors speculate that the reason for this is that the amount of solid electrolyte in contact with the electrode active material was insufficient.
[0007] In view of the above circumstances, a main object of the present disclosure is to provide an electrode for an all-solid-state battery capable of reducing battery resistance and a manufacturing method thereof. [Means for solving the problem]
[0008] As one embodiment for solving the above problems, the present disclosure provides an electrode for an all-solid-state battery, comprising an active material, a first solid electrolyte, and a second solid electrolyte, wherein the active material has an average particle size of 0.01 μm or more and 0.7 μm or less, the first solid electrolyte has an average particle size of 0.01 μm or more and 0.7 μm or less, and the second solid electrolyte has an average particle size of 0.7 μm or more and 2.0 μm or less.
[0009] In the electrode for an all-solid-state battery, the volume ratio of the first solid electrolyte to the total volume of the first solid electrolyte and the second solid electrolyte may be 20 vol% or more and 80 vol% or less. The first solid electrolyte may have an average particle size of 0.5 μm or less, and the second solid electrolyte may have an average particle size of 1.0 μm or more.
[0010] The present disclosure provides an all-solid-state battery including a first electrode, a second electrode, and a solid electrolyte layer disposed between the first electrode and the second electrode, wherein the first electrode is the all-solid-state battery electrode.
[0011] As one aspect for solving the above-mentioned problems, the present disclosure provides a method for producing an electrode for an all-solid-state battery, the method comprising: a slurry preparation step of mixing an active material, a first solid electrolyte, a second solid electrolyte, and a dispersion medium to obtain a slurry; a coating step of coating the obtained slurry onto a substrate; and a drying step of drying the slurry coated onto the substrate, wherein the active material has an average particle size of 0.01 μm or more and 0.7 μm or less, the first solid electrolyte has an average particle size of 0.01 μm or more and 0.7 μm or less, and the second solid electrolyte has an average particle size of 0.7 μm or more and 2.0 μm or less.
[0012] In the method for producing an electrode for an all-solid-state battery, the volume ratio of the first solid electrolyte to the total volume of the first solid electrolyte and the second solid electrolyte may be 20 vol% or more and 80 vol% or less. The first solid electrolyte may have an average particle size of 0.5 μm or less, and the second solid electrolyte may have an average particle size of 1.0 μm or more.
[0013] The present disclosure provides a method for manufacturing an all-solid-state battery, the method including a first electrode fabrication step of fabricating a first electrode, a second electrode fabrication step of fabricating a second electrode, a solid electrolyte layer fabrication step of fabricating a solid electrolyte layer, and a lamination step of laminating the first electrode, the second electrode, and the solid electrolyte layer such that the solid electrolyte layer is disposed between the first electrode and the second electrode, wherein the first electrode fabrication step is a method for manufacturing an electrode for the all-solid-state battery. Effect of the Invention
[0014] According to the present disclosure, the battery resistance can be reduced. [Brief description of the drawings]
[0015] [Figure 1] This shows the results of battery resistance evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] [Electrodes for all-solid-state batteries]
[0017] As a result of intensive research, the present inventors have found that the battery resistance can be reduced by using two types of solid electrolytes with different average particle sizes in an electrode and an active material with a small average particle size. This is believed to be due to an increase in the contact area between the solid electrolyte and the active material. The electrode for an all-solid-state battery disclosed herein was invented based on this finding. It will be described in detail below.
[0018] The electrode for an all-solid-state battery disclosed herein includes an active material, a first solid electrolyte, and a second solid electrolyte, wherein the active material has an average particle size of 0.01 μm or more and 0.7 μm or less, the first solid electrolyte has an average particle size of 0.01 μm or more and 0.7 μm or less, and the second solid electrolyte has an average particle size of 0.7 μm or more and 2.0 μm or less.
[0019] <Active material> The active material may be a positive electrode active material or a negative electrode active material. When the electrode is a positive electrode, a positive electrode active material is used, and when the electrode is a negative electrode, a negative electrode active material is used.
[0020] The positive electrode active material can be appropriately selected from active materials applicable to lithium ion solid-state batteries. Examples include lithium cobalt oxide, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt manganese oxide (NCM), lithium manganese oxide, etc. The surface of the positive electrode active material may be covered with an oxide layer such as a lithium niobate layer, a lithium titanate layer, or a lithium phosphate layer.
[0021] The negative electrode active material can be appropriately selected from active materials applicable to lithium ion all-solid-state batteries, such as silicon and Si alloys, tin and tin alloys, silicon-based active materials such as silicon oxide, carbon-based active materials such as graphite and hard carbon, oxide-based active materials such as lithium titanate, metallic lithium and lithium alloys.
[0022] The average particle size of the active material is 0.01 μm or more and 0.7 μm or less. By having the average particle size of the active material within this range, the contact area between the active material and the first solid electrolyte and the second solid electrolyte can be increased, and the battery resistance can be reduced. If the average particle size of the active material is less than 0.01 μm, it is difficult to prepare an electrode. If the average particle size of the active material exceeds 0.7 μm, dramatic changes may not be expected. The average particle size of the active material may be 0.1 μm or more, or may be 0.4 μm or more.
[0023] In this specification, the "average particle size" refers to the median diameter (D 50 ).
[0024] The content of the active material is not particularly limited and may be appropriately set depending on the purpose, for example, in the range of 10 wt % to 90 wt %.
[0025] <Solid electrolyte> The electrode contains two types of solid electrolytes (a first solid electrolyte and a second solid electrolyte) having different average particle sizes as the solid electrolyte, which can reduce the battery resistance and improve the filling property.
[0026] (1st solid electrolyte) The first solid electrolyte can be appropriately selected from solid electrolytes applicable to lithium ion all-solid-state batteries. For example, inorganic solid electrolyte particles such as sulfide solid electrolyte, oxide solid electrolyte, nitride solid electrolyte, halide solid electrolyte, etc. From the viewpoint of improving ion conductivity, a sulfide solid electrolyte may be used as the first solid electrolyte.
[0027] The sulfide solid electrolyte contains Li, M (M is preferably at least one of P, Ge, Si, Sn, B, and Al), and S. The sulfide solid electrolyte may further contain a halogen element. Examples of the halogen element include F, Cl, Br, and I. The amorphous sulfide solid electrolyte may further contain O.
[0028] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers. Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers; M is P, Si, Ge, B, Al, Ga, or In.)
[0029] When the sulfide solid electrolyte contains Li2S and P2S5, the ratio of Li2S to the total of Li2S and P2S5 may be in the range of 70mol% to 80mol%, may be in the range of 72mol% to 78mol%, or may be in the range of 74mol% to 76mol%. This is because the sulfide solid electrolyte can have an ortho composition or a composition close to it, and can be a sulfide solid electrolyte with high chemical stability. Here, ortho generally refers to the oxo acid obtained by hydrating the same oxide, which has the highest degree of hydration. In this specification, the crystal composition in which the most Li2S is added in the sulfide is called the ortho composition. In the Li2S-P2S5 system, Li3PS4 corresponds to the ortho composition. In the case of the sulfide solid electrolyte particles of the Li2S-P2S5 system, the ratio of Li2S and P2S5 to obtain the ortho composition is Li2S:P2S5=75:25 on a molar basis. When Al2S3 or B2S3 is used instead of P2S5, the proportion of Li2S may be within the above range. In the Li2S-Al2S3 system, Li3AlS3 corresponds to the ortho composition, and in the Li2S-B2S3 system, Li3BS3 corresponds to the ortho composition.
[0030] When the sulfide solid electrolyte contains Li2S and SiS2, the ratio of Li2S to the total of Li2S and SiS2 may be in the range of 60mol% to 72mol%, may be in the range of 62mol% to 70mol%, or may be in the range of 64mol% to 68mol%. This is because the sulfide solid electrolyte can have an ortho composition or a composition close to it, and can be a sulfide solid electrolyte with high chemical stability. In the Li2S-SiS2 system, Li4SiS4 corresponds to the ortho composition. In the case of the Li2S-SiS2 system sulfide solid electrolyte, the ratio of Li2S and SiS2 to obtain the ortho composition is Li2S:SiS2=66.6:33.3 on a molar basis. Note that, when GeS2 is used instead of SiS2, the ratio of Li2S may be within the above range. In the Li2S-GeS2 system, Li4GeS4 corresponds to the ortho composition.
[0031] When the sulfide solid electrolyte contains LiX (X=F, Cl, Br, I), the proportion of LiX may be, for example, within the range of 1 mol% to 60 mol%, 5 mol% to 50 mol%, or 10 mol% to 40 mol%. When the sulfide solid electrolyte contains Li2O, the proportion of Li2O may be, for example, within the range of 1 mol% to 25 mol%, or 3 mol% to 15 mol%.
[0032] The sulfide solid electrolyte may be a sulfide glass, a crystallized sulfide glass, or a crystalline material obtained by a solid phase method.
[0033] Examples of oxide solid electrolytes include lithium lanthanum zirconium-containing composite oxide (LLZO), Al-doped LLZO, lithium lanthanum titanium-containing composite oxide (LLTO), Al-doped LLTO, and lithium oxynitride phosphate (LIPON). Examples of nitride solid electrolytes include Li3N and Li3N-LiI-LiOH. Examples of halide solid electrolytes include LiF, LiCl, LiBr, LiI, and LiI-Al2O3.
[0034] The average particle size of the first solid electrolyte is 0.01 μm or more and 0.7 μm or less. By having the average particle size of the first solid electrolyte within the above range, the contact area between the active material and the first solid electrolyte and the second solid electrolyte can be increased, and the battery resistance can be reduced. If the average particle size of the first solid electrolyte is less than 0.01 μm, it may be difficult to prepare an electrode. If the average particle size of the first solid electrolyte exceeds 0.7 μm, dramatic changes may not be expected. The average particle size of the first solid electrolyte may be 0.1 μm or more, less than 0.7 μm, or 0.5 μm or less.
[0035] As a method for adjusting the average particle size of the first solid electrolyte, a known pulverization method can be appropriately applied. For example, a media pulverization method, a jet pulverization method, a cabination pulverization method, etc. can be mentioned. In addition, the pulverizer is not particularly limited, but for example, a bead mill, a planetary ball mill, etc. can be mentioned. The pulverization conditions can be appropriately set so as to obtain a first solid electrolyte having a desired average particle size.
[0036] The BET specific surface area of the first solid electrolyte is not particularly limited. For example, the BET specific surface area of the first solid electrolyte is 20 m 2 / g or more is acceptable, and 40m 2 / g or less. The BET specific surface area of the first solid electrolyte may be 20 m 2 If the BET specific surface area of the first solid electrolyte is less than 40 m / g, the particle size becomes large and the effect may not be obtained. 2 If the content exceeds 1 / g, the particle size becomes finer, but there is a risk that electrode production becomes more difficult.
[0037] The BET specific surface area can be measured by the BET method.
[0038] (Second solid electrolyte) The second solid electrolyte can be appropriately selected from solid electrolytes applicable to lithium ion all-solid-state batteries. For example, it may be appropriately selected from solid electrolytes applicable to the first solid electrolyte. However, the second solid electrolyte may be the same type of solid electrolyte as the first solid electrolyte, or may be a different type of solid electrolyte.
[0039] The average particle size of the second solid electrolyte is 0.7 μm or more and 2.0 μm or less. By having the average particle size of the second solid electrolyte within the above range, the contact area between the active material and the first solid electrolyte and the second solid electrolyte can be increased, and the battery resistance can be reduced. If the average particle size of the second solid electrolyte is less than 0.7 μm, the electrolytes have small particle sizes, which may reduce the contact area. If the average particle size of the second solid electrolyte exceeds 2.0 μm, the contact area may also be reduced. The average particle size of the second solid electrolyte may be 1.0 μm or more and 1.6 μm or less.
[0040] Here, the second solid electrolyte is characterized by having a larger average particle size than the first solid electrolyte. For example, when the average particle size of the second solid electrolyte is 0.7 μm, the average particle size of the first solid electrolyte is set to less than 0.7 μm. Also, when the average particle size of the first solid electrolyte is 0.7 μm, the average particle size of the second solid electrolyte is set to more than 0.7 μm. The difference in average particle size between the first solid electrolyte and the second solid electrolyte may be, for example, 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, 1.9 μm or less, 1.7 μm or less, or 1.5 μm or less.
[0041] As a method for adjusting the average particle size of the second solid electrolyte, a known pulverization method can be appropriately applied. For example, a media pulverization method, a jet pulverization method, a cabination pulverization method, etc. can be mentioned. In addition, the pulverizer is not particularly limited, but for example, a bead mill, a planetary ball mill, etc. can be mentioned. The pulverization conditions can be appropriately set so as to obtain a second solid electrolyte having a desired average particle size.
[0042] The BET specific surface area of the second solid electrolyte is not particularly limited. For example, the BET specific surface area of the second solid electrolyte is 5 m 2 / g or more is acceptable, and 15m 2 / g or less. The BET specific surface area of the second solid electrolyte may be 5 m 2 If the BET specific surface area of the second solid electrolyte is less than 15 m / g, the particle size becomes large and the contact area may decrease. 2 / g, there is a possibility that the contact area will decrease.
[0043] (Content of first solid electrolyte and second solid electrolyte) The total content of the first solid electrolyte and the second solid electrolyte is not particularly limited and may be set appropriately, for example, in the range of 1 wt % to 90 wt %.
[0044] (Ratio of first solid electrolyte and second solid electrolyte) The ratio of the first solid electrolyte and the second solid electrolyte is not particularly limited. For example, the volume ratio of the first solid electrolyte to the total volume (100vol%) of the first solid electrolyte and the second solid electrolyte may be 10vol% or more, 20vol% or more, 50vol% or more, less than 100vol%, 90vol% or less, 80vol% or less, or 70vol% or less. The larger the volume ratio of the first solid electrolyte, the more the battery resistance can be reduced, but if the volume ratio of the first solid electrolyte is too large, the viscosity of the slurry used in preparing the electrode increases, and the coatability and moldability decrease. From the viewpoint of reducing the battery resistance and improving the coatability and moldability, the volume ratio of the first solid electrolyte may be 20vol% or more and 80vol% or less, or 50vol% or more and 80vol% or less.
[0045] <Other ingredients> The electrode for the all-solid-state battery may optionally contain a conductive assistant. The conductive assistant can be appropriately selected from conductive assistants applicable to lithium-ion all-solid-state batteries. Examples of the conductive assistant include carbon materials such as acetylene black, ketjen black, and vapor-grown carbon fiber (VGCF), and metal materials such as nickel, aluminum, and stainless steel. The content of the conductive assistant is not particularly limited, but is, for example, in the range of 0.1 wt% to 10 wt%.
[0046] In addition, the electrode for the all-solid-state battery may contain a binder as desired. The binder can be appropriately selected from binders applicable to lithium-ion all-solid-state batteries. Examples include butadiene rubber (BR), butylene rubber (IIR), acrylate butadiene rubber (ABR), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVdF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), etc. The content of the binder is not particularly limited, but is, for example, in the range of 0.1 wt% to 10 wt%.
[0047] <Electrode> The electrode may be a positive electrode or a negative electrode. The shape of the electrode is not particularly limited, but may be a sheet. The thickness of the electrode is not particularly limited, but may be, for example, in the range of 0.1 μm to 1 mm.
[0048] The method for producing the electrode is not particularly limited. For example, the electrode may be produced by mixing the materials constituting the electrode and pressing them. Alternatively, the electrode may be produced by dispersing the materials constituting the electrode in a dispersant to form a slurry, and then applying the slurry to a predetermined substrate and drying it. The method for producing the electrode using the slurry will be described in detail later.
[0049] In the all-solid-state battery electrode of the present disclosure, the average particle sizes of the active material, the first solid electrolyte, and the second solid electrolyte are adjusted within a predetermined range, thereby making it possible to increase the contact area between the positive electrode active material and the solid electrolytes (the first solid electrolyte and the second solid electrolyte) and reduce the battery resistance.
[0050] [All-solid battery] The all-solid-state battery of the present disclosure is characterized by including the above-mentioned all-solid-state battery electrode. Specifically, the all-solid-state battery of the present disclosure includes a first electrode, a second electrode, and a solid electrolyte layer disposed between the first electrode and the second electrode, and the first electrode is the above-mentioned all-solid-state battery electrode. The all-solid-state battery of the present disclosure can reduce battery resistance by including the above-mentioned all-solid-state battery electrode.
[0051] <1st electrode> Since the first electrode is the electrode for the all-solid-state battery described above, a description thereof will be omitted here.
[0052] <Second electrode> The second electrode is a negative electrode when the first electrode is a positive electrode, and is a positive electrode when the first electrode is a negative electrode.
[0053] When the second electrode is a positive electrode, the second electrode contains a positive electrode active material. The positive electrode active material is not particularly limited, and can be appropriately selected from positive electrode active materials applicable to lithium ion all-solid-state batteries. For example, the positive electrode active material applicable to the electrodes for all-solid-state batteries described above can be used. When the second electrode is a negative electrode, the second electrode contains a negative electrode active material. The negative electrode active material is not particularly limited, and can be appropriately selected from positive electrode active materials applicable to lithium ion all-solid-state batteries. For example, the negative electrode active material applicable to the electrodes for all-solid-state batteries described above can be used. The content of the positive electrode active material or the negative electrode active material in the second electrode is not particularly limited. For example, it may be in the range of 10 wt% to 90 wt%.
[0054] The second electrode may optionally contain a solid electrolyte. The solid electrolyte is not particularly limited and can be appropriately selected from solid electrolytes applicable to lithium ion all-solid-state batteries. For example, the solid electrolytes applicable to the electrodes for all-solid-state batteries described above can be mentioned. The content of the solid electrolyte in the second electrode is not particularly limited. For example, it may be in the range of 1 wt% to 90 wt%.
[0055] The second electrode may contain an optional conductive assistant. The conductive assistant is not particularly limited, and can be appropriately selected from conductive assistants applicable to lithium ion all-solid-state batteries. For example, the conductive assistants applicable to the electrodes for all-solid-state batteries described above can be mentioned. The content of the conductive assistant in the second electrode is not particularly limited. For example, it may be in the range of 0.1 wt% to 10 wt%.
[0056] The second electrode may contain an arbitrary binder. The binder is not particularly limited, and can be appropriately selected from binders applicable to lithium ion all-solid-state batteries. For example, the binders applicable to the electrodes for all-solid-state batteries described above can be mentioned. The content of the binder in the second electrode is not particularly limited. For example, it may be in the range of 0.1 wt% to 10 wt%.
[0057] The shape of the second electrode is not particularly limited, but may be a sheet. The thickness of the second electrode is not particularly limited, but may be, for example, in the range of 0.1 μm to 1 mm.
[0058] <Solid electrolyte layer> The solid electrolyte layer includes a solid electrolyte. The solid electrolyte is not particularly limited, and can be appropriately selected from solid electrolytes applicable to lithium ion all-solid-state batteries. For example, the solid electrolyte applicable to the above-mentioned all-solid-state battery electrodes can be mentioned. The content of the solid electrolyte in the solid electrolyte layer is not particularly limited. For example, it is in the range of 50wt% to 99wt%. The range may be as follows.
[0059] The solid electrolyte layer may contain any binder. The binder is not particularly limited, and can be appropriately selected from binders applicable to lithium ion all-solid-state batteries. For example, the binder applicable to the above-mentioned all-solid-state battery electrodes can be mentioned. The content of the binder in the solid electrolyte layer is not particularly limited. For example, it may be in the range of 0.1 wt% to 10 wt%.
[0060] The shape of the solid electrolyte layer is not particularly limited, but may be a sheet. The thickness of the solid electrolyte layer is not particularly limited, but may be, for example, in the range of 0.1 μm to 1 mm. <Other materials> The all-solid-state battery may optionally include a current collector (positive electrode current collector and negative electrode current collector). The material of the current collector is not particularly limited and can be appropriately selected from known materials depending on the purpose. For example, Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc. are included. The thickness of the current collector is not particularly limited and may be appropriately set depending on the desired battery performance. For example, it is in the range of 0.1 μm to 1 mm.
[0061] The all-solid-state battery of the present disclosure may be a single cell or a stacked battery. The stacked battery may be a monopolar stacked battery (a parallel-connected stacked battery) or a bipolar stacked battery (a series-connected stacked battery). The shape of the all-solid-state battery may be, for example, a coin type, a laminate type, a cylindrical type, or a square type.
[0062] [Method of manufacturing electrodes for all-solid-state batteries] The manufacturing method for an electrode for an all-solid-state battery disclosed herein includes a slurry preparation step of mixing an active material, a first solid electrolyte, a second solid electrolyte, and a dispersion medium to obtain a slurry, a coating step of coating the obtained slurry onto a substrate, and a drying step of drying the slurry coated onto the substrate, wherein the active material has an average particle size of 0.01 μm or more and 0.7 μm or less, the first solid electrolyte has an average particle size of 0.01 μm or more and 0.7 μm or less, and the second solid electrolyte has an average particle size of 0.7 μm or more and 2.0 μm or less.
[0063] <Slurry preparation process> The slurry preparation process is a process of mixing an active material, a first solid electrolyte, a second solid electrolyte, and a dispersion medium to obtain a slurry. The types and contents of the active material, the first solid electrolyte, and the second solid electrolyte have been described above, and therefore will not be described here. The dispersion medium is not particularly limited, and a known organic solvent can be used. For example, hexane and DIBK (diisobutyl ketone) can be used.
[0064] The viscosity of the slurry is not particularly limited, but may be, for example, in the range of 100 mPa·s to 5000 mPa·s. If the viscosity of the slurry exceeds 5000 mPa·s, the coating property and moldability of the slurry deteriorate. From the viewpoint of further improving the coating property and moldability of the slurry, the viscosity of the slurry may be 3000 mPa·s or less, or may be 2000 mPa·s or less.
[0065] In this specification, the viscosity of the slurry is a value measured by the following method. 1 ml of the prepared slurry is taken and measured at a shear rate of 38.3 S using an E-type viscometer. -1 The viscosity of the slurry during this step is measured.
[0066] The solid content of the slurry is not particularly limited and can be set appropriately, for example, to 10 wt % or more and 80 wt % or less.
[0067] <Coating process> The coating step is a step of coating the obtained slurry on a substrate. The substrate to which the slurry is applied is not particularly limited, and may be a metal foil, a current collector, or a solid electrolyte layer. The coating method may be a known method. For example, general methods such as a doctor blade method, a die coating method, a gravure coating method, a spray coating method, an electrostatic coating method, and a bar coating method may be mentioned.
[0068] <Drying process> The drying step is a step of drying the slurry applied to the substrate. The drying step can be performed by a known method. For example, the slurry may be heated to a temperature range of 50° C. to 200° C. The atmosphere may be set to an inert atmosphere or a reduced pressure atmosphere.
[0069] [Manufacturing method of all-solid-state batteries] The manufacturing method of the all-solid-state battery disclosed herein includes a first electrode fabrication step of fabricating a first electrode, a second electrode fabrication step of fabricating a second electrode, a solid electrolyte layer fabrication step of fabricating a solid electrolyte layer, and a lamination step of laminating the first electrode, the second electrode, and the solid electrolyte layer such that the solid electrolyte layer is disposed between the first electrode and the second electrode, and the first electrode fabrication step is the manufacturing method of an electrode for an all-solid-state battery.
[0070] <First electrode fabrication process> The first electrode preparation step is the same as the method for producing an electrode for an all-solid-state battery as described above, and therefore a description thereof will be omitted here.
[0071] <Second electrode fabrication process> The second electrode preparation step can be carried out by a known method. For example, the second electrode may be manufactured by mixing the materials constituting the second electrode and pressing them. Alternatively, the materials constituting the second electrode may be dispersed in a dispersant to form a slurry, and then the slurry may be applied to a predetermined substrate and dried to manufacture the electrode.
[0072] <Solid electrolyte layer production process> The solid electrolyte layer preparation step can be carried out by a known method. For example, the solid electrolyte layer may be produced by mixing and pressing the materials constituting the solid electrolyte layer. Alternatively, the solid electrolyte layer may be produced by dispersing the materials constituting the solid electrolyte layer in a dispersant to form a slurry, and then applying the slurry to a predetermined substrate and drying it.
[0073] <Lamination process> The lamination step is a step of laminating a first electrode, a second electrode, and a solid electrolyte layer so that the solid electrolyte layer is disposed between the first electrode and the second electrode. The lamination step may simply laminate these layers, or may involve pressing after lamination. The pressing method is not particularly limited, and examples thereof include roll pressing and plate pressing. The linear pressure applied during roll pressing may be, for example, 1 t / cm or more and 10 t / cm or less. The surface pressure applied during plate pressing may be, for example, 800 MPa or more and 3000 MPa or less.
[0074] If necessary, for example, after or before the lamination step, a negative electrode current collector may be placed on the surface of the negative electrode active material layer, and a positive electrode current collector may be placed on the surface of the positive electrode active material layer. EXAMPLES
[0075] [Fabrication of all-solid-state batteries] As described below, all-solid-state batteries were fabricated according to Examples 1 to 81, Reference Examples 1 to 18, and Comparative Examples 1 to 18. Tables 1 to 3 show the physical properties of each component.
[0076] <Examples 1 to 9> (Preparation of sulfide solid electrolyte) Li2S and P2S5 were weighed to obtain a raw material composition with a molar ratio of Li2S:P2S5=75:25. This raw material composition and tetrahydrofuran, which was 20 times the weight ratio of the raw material composition, were placed in a glass container and stirred at 25°C for 72 hours, and the precipitated powder was collected as a precursor of the sulfide solid electrolyte. The collected precursor was dried at 25°C under an argon atmosphere and then fired (first firing) at 100°C under atmospheric pressure (open system) for 1 hour. The obtained fired body was vacuum sealed in a quartz tube, and the quartz tube was fired (second firing) at 140°C for 12 hours in a muffle furnace to produce a sulfide solid electrolyte. The obtained sulfide solid electrolyte was pulverized using a planetary ball mill (manufactured by Fritsch) to adjust the average particle size, and the first solid electrolyte and the second solid electrolyte used in Examples 1 to 9 were produced.
[0077] (Negative electrode manufacturing process) 18.6g of negative electrode active material particles (Si), 0.09g of the first solid electrolyte, 8.6g of the second solid electrolyte, 2.4g of the conductive additive (VGCF), and a binder (SBR) diluted to 5wt% were put into a dispersion medium (DIBK) and mixed. The volume ratio of the first solid electrolyte and the second solid electrolyte was 10:90 (vol%). The solid content rate was 43wt%. A Filmix was used as a kneading device, and these materials were kneaded at a peripheral speed in the range of 5m / s to 30m / s to prepare a negative electrode slurry. A high shear PC wheel was used for the Filmix. The viscosity of the obtained negative electrode slurry was measured. The slurry viscosity shown in Table 1 is the average value of the slurry viscosities of Examples 1 to 9.
[0078] The negative electrode slurry was applied onto a negative electrode current collector by a blade coating method using an applicator, and dried under conditions of 100° C. for 30 minutes to obtain a negative electrode having a negative electrode layer on the negative electrode current collector.
[0079] (Positive electrode manufacturing process) Cathode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 80.0g of O2), 9.51g of sulfide solid electrolyte (LPS), and 2.0g of conductive additive (VGCF) were collected in a Filmix container. Then, SBR as a binder diluted to 5wt% and 32.21g of tetralin as a dispersion medium were added to the container so that the solid content was 69wt%. A Filmix was used as a kneading device, and these materials were kneaded at a peripheral speed of 5m / s to 30m / s to prepare a positive electrode layer paste. The obtained positive electrode layer paste was applied to a positive electrode current collector by a blade coat method using an applicator, and dried at 100°C for 30 minutes to obtain an electrode having a positive electrode layer on a positive electrode current collector.
[0080] (Solid electrolyte layer production process) 40 g of sulfide solid electrolyte (LPS), 8.00 g of a solution in which 5 wt% ABR was dissolved in heptane solution, 25.62 g of heptane as a solvent, and 8.00 g of dibutyl ether were mixed and kneaded with an ultrasonic homogenizer. The obtained solid electrolyte layer paste was applied to an Al foil current collector by the blade coating method with an applicator, and dried at 100°C for 30 minutes to obtain an electrode with a solid electrolyte layer.
[0081] (Lamination process) The negative electrode, the positive electrode, and the solid electrolyte layer were laminated so that the solid electrolyte layer was disposed between the negative electrode and the positive electrode, and various current collectors and terminals were attached to fabricate the all-solid-state batteries of Examples 1 to 9.
[0082] <Examples 10 to 18> The all-solid-state batteries of Examples 10 to 18 were produced in the same manner as in Examples 1 to 9, except that in the negative electrode production process, the weight of the first solid electrolyte was changed to 1.9 g, the weight of the second solid electrolyte was changed to 7.6 g, the volume ratio of the first solid electrolyte to the second solid electrolyte was changed to 20:80 (vol%), and the solid content rate was changed to 42 wt%.
[0083] <Examples 19 to 27> The all-solid-state batteries of Examples 19 to 27 were produced in the same manner as in Examples 1 to 9, except that in the negative electrode production process, the weight of the first solid electrolyte was changed to 2.8 g, the weight of the second solid electrolyte was changed to 6.7 g, the volume ratio of the first solid electrolyte to the second solid electrolyte was changed to 30:70 (vol%), and the solid content rate was changed to 41 wt%.
[0084] <Examples 28 to 36> The all-solid-state batteries of Examples 28 to 36 were produced in the same manner as in Examples 1 to 9, except that in the negative electrode production process, the weight of the first solid electrolyte was changed to 3.8 g, the weight of the second solid electrolyte was changed to 5.7 g, the volume ratio of the first solid electrolyte to the second solid electrolyte was changed to 40:60 (vol%), and the solid content rate was changed to 38 wt%.
[0085] <Examples 37 to 45> The all-solid-state batteries of Examples 37 to 45 were produced in the same manner as in Examples 1 to 9, except that in the negative electrode production process, the weight of the first solid electrolyte was changed to 4.7 g, the weight of the second solid electrolyte was changed to 4.8 g, the volume ratio of the first solid electrolyte and the second solid electrolyte was changed to 50:50 (vol%), and the solid content rate was changed to 36 wt%.
[0086] <Examples 46 to 54> The all-solid-state batteries of Examples 46 to 54 were produced in the same manner as in Examples 1 to 9, except that in the negative electrode production process, the weight of the first solid electrolyte was changed to 5.6 g, the weight of the second solid electrolyte was changed to 3.8 g, the volume ratio of the first solid electrolyte to the second solid electrolyte was changed to 60:40 (vol%), and the solid content rate was changed to 34 wt%.
[0087] <Examples 55 to 63> The all-solid-state batteries of Examples 55 to 63 were produced in the same manner as in Examples 1 to 9, except that in the negative electrode production process, the weight of the first solid electrolyte was changed to 6.6 g, the weight of the second solid electrolyte was changed to 2.9 g, the volume ratio of the first solid electrolyte to the second solid electrolyte was changed to 70:30 (vol%), and the solid content rate was changed to 32 wt%.
[0088] <Examples 64 to 72> The all-solid-state batteries of Examples 64 to 72 were produced in the same manner as in Examples 1 to 9, except that in the negative electrode production process, the weight of the first solid electrolyte was changed to 7.5 g, the weight of the second solid electrolyte was changed to 1.9 g, the volume ratio of the first solid electrolyte to the second solid electrolyte was changed to 80:20 (vol%), and the solid content rate was changed to 30 wt%.
[0089] <Examples 73 to 81> The all-solid-state batteries of Examples 73 to 81 were produced in the same manner as in Examples 1 to 9, except that in the negative electrode production process, the weight of the first solid electrolyte was changed to 8.5 g, the weight of the second solid electrolyte was changed to 1.0 g, the volume ratio of the first solid electrolyte to the second solid electrolyte was changed to 90:10 (vol%), and the solid content rate was changed to 28 wt%.
[0090] <Reference examples 1~9> All-solid-state batteries of Reference Examples 1 to 9 were produced in the same manner as in Examples 1 to 9, except that in the negative electrode production process, the first solid electrolyte was not used, the weight of the second solid electrolyte was changed to 9.5 g, and the solid content rate was changed to 43 wt %.
[0091] <Reference examples 10~18> All-solid-state batteries of Reference Examples 10 to 18 were produced in the same manner as in Examples 1 to 9, except that in the negative electrode production process, the second solid electrolyte was not used, the weight of the first solid electrolyte was changed to 9.5 g, and the solid content rate was changed to 26 wt %.
[0092] <Comparative Examples 1 to 3> All-solid-state batteries of Comparative Examples 1 to 3 were produced in the same manner as in Examples 10, 14 and 18, except that a negative electrode active material having an average particle size of 2 μm was used in the negative electrode production step.
[0093] <Comparative Examples 4 to 6> All-solid-state batteries of Comparative Examples 4 to 6 were produced in the same manner as in Examples 37, 41 and 45, except that a negative electrode active material having an average particle size of 2 μm was used in the negative electrode production step.
[0094] <Comparative Examples 7 to 9> All-solid-state batteries of Comparative Examples 7 to 9 were produced in the same manner as in Examples 64, 68 and 72, except that a negative electrode active material having an average particle size of 2 μm was used in the negative electrode production step.
[0095] <Comparative Examples 10 to 12> All-solid-state batteries of Comparative Examples 10 to 12 were produced in the same manner as in Examples 10, 14 and 18, except that a negative electrode active material having an average particle size of 3 μm was used in the negative electrode production step.
[0096] <Comparative Examples 13 to 15> All-solid-state batteries of Comparative Examples 13 to 15 were produced in the same manner as in Examples 37, 41 and 45, except that a negative electrode active material having an average particle size of 3 μm was used in the negative electrode production step.
[0097] <Comparative Examples 16 to 18> All-solid-state batteries of Comparative Examples 16 to 18 were produced in the same manner as in Examples 64, 68 and 72, except that a negative electrode active material having an average particle size of 3 μm was used in the negative electrode production step.
[0098] [Battery resistance evaluation] Using the produced all-solid-state battery, CCCV charging and discharging was performed at 0.1 C from an upper limit voltage of 4.05 V to a lower limit voltage of 2.5 V. The design capacity of the all-solid-state battery was 0.3 Ah. The battery resistance was calculated from the obtained results. The results are shown in Tables 1 to 3. FIG. 1 shows the relationship between the proportion of the first solid electrolyte and the battery resistance (average value). In FIG. 1, examples are shown with "◯", reference examples with "□", and comparative examples with "△".
[0099] [Table 1]
[0100] [Table 2]
[0101] [Table 3]
[0102] Comparing Examples 1 to 81 with Comparative Examples 1 to 18, it was confirmed that the battery resistance was low in Examples 1 to 81, which used a negative electrode active material with a small average particle size, and the battery resistance was high in Comparative Examples 1 to 18, which used a negative electrode active material with a large average particle size. On the other hand, when the results of Examples 1 to 9 were examined, for example, the magnitude of the battery resistance was almost the same if the negative electrode active material had an average particle size of 0.7 or less.
[0103] Next, by comparing Examples 1 to 81 with Reference Examples 1 to 18, it was found that the battery resistance tends to decrease as the proportion of the first solid electrolyte increases. On the other hand, it was also found that the viscosity of the negative electrode slurry tends to increase as the proportion of the first solid electrolyte increases. Considering the magnitude of the battery resistance and the slurry viscosity, it is considered that Examples 1 to 81 in which the first solid electrolyte and the second solid electrolyte are mixed are superior to Reference Examples 1 to 18 in which only the first solid electrolyte or the second solid electrolyte is included.
[0104] [SEM analysis] The cross section of the negative electrode was analyzed using SEM. The magnification of the SEM was set to 2000 times, and five arbitrary points were observed. The SEM image of the negative electrode cross section obtained was imported into ImageJ, and the total length of the solid electrolyte in contact with the active material (contact length of the solid electrolyte) was calculated by image analysis. The results of Example 55 and Comparative Example 34 are shown in Table 4.
[0105] [Table 4]
[0106] As shown in Table 4, the longer the contact length of the solid electrolyte, the lower the battery resistance. Since the contact length correlates with the number of solid electrolytes in contact with the negative electrode active material, it is considered that the longer the contact length, the more solid electrolytes are in contact with the negative electrode active material. From this, it is considered that the battery resistance is reduced by increasing the contact area between the solid electrolyte and the negative electrode active material.
Claims
1. A battery comprising a negative electrode active material, a first solid electrolyte, and a second solid electrolyte, The average particle size of the negative electrode active material is 0.01 μm or more and 0.7 μm or less, The first solid electrolyte has an average particle size of 0.01 μm or more and 0.5 μm or less, The second solid electrolyte has an average particle size of 1.0 μm or more and 2.0 μm or less, the negative electrode active material is Si or a Si alloy, the first solid electrolyte and the second solid electrolyte are Li 2 S—P 2 S 5 , a volume ratio of the first solid electrolyte to a total volume of the first solid electrolyte and the second solid electrolyte is 20 vol% or more and 80 vol% or less, By including two types of solid electrolytes with different average particle sizes, the filling property is improved. Electrodes for all-solid-state batteries.
2. 2. The electrode for an all-solid-state battery according to claim 1, wherein a volume ratio of the first solid electrolyte to a total volume of the first solid electrolyte and the second solid electrolyte is 30 vol% or more and 80 vol% or less.
3. a first electrode, a second electrode, and a solid electrolyte layer disposed between the first electrode and the second electrode; The first electrode is the electrode for an all-solid-state battery according to claim 1 or 2. all solid state battery
4. A slurry preparation process of mixing a negative electrode active material, a first solid electrolyte, a second solid electrolyte, and a dispersion medium to obtain a slurry; A coating step of coating the obtained slurry onto a substrate; A drying step of drying the slurry applied to the base material, The average particle size of the active material is 0.01 μm or more and 0.7 μm or less, The first solid electrolyte has an average particle size of 0.01 μm or more and 0.5 μm or less, The second solid electrolyte has an average particle size of 1.0 μm or more and 2.0 μm or less, the negative electrode active material is Si or a Si alloy, the first solid electrolyte and the second solid electrolyte are Li 2 S—P 2 S 5 , A volume ratio of the first solid electrolyte to a total volume of the first solid electrolyte and the second solid electrolyte is 20 vol% or more and 80 vol% or less. A method for manufacturing electrodes for all-solid-state batteries.
5. 5. The method for producing an electrode for an all-solid-state battery according to claim 4, wherein a volume ratio of the first solid electrolyte to a total volume of the first solid electrolyte and the second solid electrolyte is 30 vol% or more and 80 vol% or less.
6. a first electrode fabrication step of fabricating a first electrode; a second electrode fabrication step of fabricating a second electrode; a solid electrolyte layer preparation step of preparing a solid electrolyte layer; a lamination step of laminating the first electrode, the second electrode, and the solid electrolyte layer such that the solid electrolyte layer is disposed between the first electrode and the second electrode, The first electrode preparation step is a method for producing an electrode for an all-solid-state battery according to claim 4 or 5. How solid-state batteries are manufactured.
Citation Information
Patent Citations
All solid battery
JP2013157084A
All-solid-state lithium ion secondary battery
JP2014035818A
Sulfide solid battery
JP2019212430A
All-solid battery and manufacturing method thereof
JP2020021674A
Negative electrode material for solid battery, and solid battery
JP2020198254A